The treatment of automotive workshop wastewater using electrocoagulation process - Monik Kasman; Salmariza Sy; Anggrika Riyanti; Hendi Matalata; Irpan Firfansyah (Jurnal Litbang Industri, 2023)
Automotive workshop activities generate waste water requiring some treatments before being discharged into receiving water surface. One of the wastewater treatment methods for is the electrocoagulation method. This study aims to observe the effectiveness of the electrocoagulation method in treating wastewater from automotive workshop activities. Observations were limited to the effect of current density on the efficiency of removal of pollutants from wastewater from automotive workshop activities, including pH, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) ,oil and grease Current density were varied into 62 A/m2, 53 A/m 2, and 31 A/m 2. The results showed that the highest removal efficiency for the pollutant parameters BOD, COD, and oil and grease respectively were 91.53%, 94.90%, and 81,38% at current density 62 A/m 2. The electrocoagulation process was strongly influenced by the current density, where the higher the current density, the higher the removal efficiency.